Prevalencia serológica de la enfermedad influenza aviar en aves de traspatio de la provincia de Loja - Tandazo Chamba, Ángel Medardo (2019)
The present cross-sectional observational study aimed to determine the serological prevalence of Avian Influenza virus in backyard birds in the province of Loja. A total of 276 samples of bird blood were obtained in backyard farms due to alar puncture of the cantons: Loja, Chaguarpamba, Catamayo and Zapotillo. The farms included in the study were located near wetlands and commercial poultry. An epidemiological survey was applied in each of the properties, to collect information about the following variables: origin (parish and canton), management of more than one poultry exploitation system and risk factors that influence the presence of this disease as It is close to wetlands among others. Blood samples collected were subjected to serology by indirect ELISA with the Avian Influenza antibody test kit (BioChek) for detection of Avian Influenza virus (LP H7N1, H9N2, LP H5N2, or H6N2); Of the 276 samples, 4 positive samples resulted with a percentage of (1.44%), and 272 negative samples with a percentage of 98.56%. In the cantons Loja, Chaguarpamba, Catamayo and Zapotillo had an equal result of 0.36% one in each canton. Among the species analyzed rooster and chicken had a prevalence of 0.72% while in geese the prevalence was 0%; must be ratified by confirmatory tests such as PCR. Regarding the variables mentioned in this study, according to the statistical analysis, the Test. Fisher being p values less than 1 as statistically non-significant, the p value of the cantons is (p value = 0.2369), in terms of the production of commercial birds and species of birds the (p value = 1). Regarding vaccinated birds, the (p value = 1). As we can say that no associated factor was found that influences Avian Influenza disease near wetlands and poultry farms. Concluding that this disease does not represent risks for commercial poultry production in the period in which this study was carried out. Key words: avian influenza, serological prevalence, backyard, wetlands, risk factors.